Transiusnaturalismo. Acercamiento a una fundamentación pluri-moral de los derechos humanos - Reyes Negrete, Jorge (2026)
Is there a single moral sense? The invitation, then, is to think and re-think the kind of morality that provides human rights with content in the West regarding plurality. Speaking of a single morality would be to (re)affirm the existence of a cultural supremacy. Hence, there is the need to construct discourses of human rights -yes, in the plural. It is here where the quali-democratic leap called transiusnaturalism finds place.